Strategije raziskovanja in poučevanja pismenosti - Petek, Tomaž (Šolsko polje, 2012)
The article is a theoretical discussion about research and literacy teaching strategies with an emphasis on reading literacy. It is especially intended for teachers giving lessons. The models of learning to read, making realization of reading literacy possible, are presented and a lot of attention is given to the evaluation of students' reading comprehension (reading evaluation aims, reading evaluation on the local and state level and different adjustment criteria for the recognition of reading disorders, the evaluation of reading that helps with teaching, measuring knowledge on the basis of the curriculum, etc.). Since reading and writing are two directly related activities, a concrete model exemplifies the correlation of reading and writing, and the direct relation with practical work is indicated on the evaluation model CLAS-Plus, which we have adapted to the Slovene educational system.
Keywords: branje; reading literacy; researching literacy; bralna pismenost; teaching literacy; raziskovanje; reading models; poučevanje; evaluation; modeli branja; ocenjevanje; education; organizacija pouka